1990
DOI: 10.1128/jvi.64.7.3399-3406.1990
|View full text |Cite
|
Sign up to set email alerts
|

Interference with human immunodeficiency virus (HIV) replication by CD8+ T cells in peripheral blood leukocytes of asymptomatic HIV carriers in vitro

Abstract: A long asymptomatic period is one of the characteristics of human immunodeficiency virus (HIV) infection, despite its fatal consequences. Antiviral defense in HIV-infected individuals controls viral replication during this period. In the present study, we demonstrate that peripheral blood leukocytes (PBL) of asymptomatic HIV-1 carriers, following exogenous HIV-1 infection in vitro, do not support viral replication. These cells do not produce detectable amounts of reverse transcriptase or accumulate unintegrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…The cellular arm of the immune response plays a critical role in the host's defense against viral infections and the CD8+ T-lymphocytes form an important part of this cellular immunity. The antiviral activity of CD8+ T-lymphocytes has been demonstrated in HIV-1-infected humans and chimpanzees [8,10,29]. Walker et al [54] demonstrated that CD8+ T-lymphocytes from asymptomatic HIV-infected individuals suppressed HIV replication in cultured PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular arm of the immune response plays a critical role in the host's defense against viral infections and the CD8+ T-lymphocytes form an important part of this cellular immunity. The antiviral activity of CD8+ T-lymphocytes has been demonstrated in HIV-1-infected humans and chimpanzees [8,10,29]. Walker et al [54] demonstrated that CD8+ T-lymphocytes from asymptomatic HIV-infected individuals suppressed HIV replication in cultured PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although we measured here the splenic lymphocyte response to the p24 antigen as an indicator for evaluating cellular immunity, it is important to further clarify whether our recombinants, especially vac-gag/pol, are able to induce cytotoxic T cells against the cells expressing the gag antigen. If they have such an ability, we could expect that they interfere with the onset of AIDS from asymptomatic HIV carrier (15).…”
Section: Immune Response Of Alice Of Different Strainsmentioning
confidence: 99%
“…We and others have shown that such CD8 ϩ cellmediated suppression is common in the PBMC of AC but rare in uninfected individuals or AIDS patients (15,23), implying that CD8 ϩ cell-mediated suppression may play an important role in maintaining an asymptomatic state. Furthermore, this protection is effective against not only endogenous but also exogenous infective laboratory strains of HIV-1 (15). Similar CD8 ϩ cell-mediated suppression of virus replication is ob-served in simian immunodeficiency virus-infected macaques and HIV-1-infected chimpanzees in vitro (4,16).…”
mentioning
confidence: 83%
“…Removal of CD8 ϩ cells from the culture allows active virus replication in the remaining cells, indicating that CD8 ϩ T lymphocytes of AC suppress HIV-1 multiplication (37). We and others have shown that such CD8 ϩ cellmediated suppression is common in the PBMC of AC but rare in uninfected individuals or AIDS patients (15,23), implying that CD8 ϩ cell-mediated suppression may play an important role in maintaining an asymptomatic state. Furthermore, this protection is effective against not only endogenous but also exogenous infective laboratory strains of HIV-1 (15).…”
mentioning
confidence: 83%